Accelerometry in sport - Lukášek, M.; Vychodilová, R. (Journal of Human Sport & Exercise, 2016)
The possibilities to analyse various sports movements and activities, their techniques and dynamics are deepening and enhancing with the rapid development of modern technologies. It subsequently enables to improve and enhance sports techniques, performances and efficiency, to prevent possible injuries, to enhance training methods, and to reach sports results of higher quality. The use of accelerometry to observe, examine and analyse various movements and their techniques and dynamics in different human physical and sports activities has become of high prominence in several recent decades. The goal of the paper is to illustrate some possibilities of the use of accelerometry to analyse these aspects in the field of sport, in selected cyclic and acyclic sports. The study aims to outline and indicate a way of possible examination, observation and analysis of the data acquired by accelerometry measurements.